Financial Repression is Knocking at the Door, Again - Jafarov, Etibar (IMF Working Papers; Working Paper ;, 2019)
Financial repression (legal restrictions on interest rates, credit allocation, capital movements, and other financial operations) was widely used in the past but was largely abandoned in the liberalization wave of the 1990s, as widespread support for interventionist policies gave way to a renewed conception of government as an impartial referee. Financial repression has come back on the agenda with the surge in public debt in the wake of the Global Financial Crisis, and some countries have reintroduced administrative ceilings on interest rates. By distorting market incentives and signals, financial repression induces losses from inefficiency and rent-seeking that are not easily quantified. This study attempts to assess some of these losses by estimating the impact of financial repression on growth using an updated index of interest rate controls covering 90 countries over 45 years. The results suggest that financial repression poses a significant drag on growth, which could amount to 0.4-0.7 percentage points.